Refleksie op twee pastorale modelle, Deel 1: Die pastor as vertolker - die ontmoetingsmodel - Dreyer, Yolanda (Hervormde teologiese studies, 1999)
Relection on two models in pastoral theology, Part 1: The pas-tor as interpreter - a model of encountering. This article focuses on models for pastoral care. Two aspects of the so-called "model of encountering" are discussed, namely the role of the pastor in pastoral interaction, and Scripture as the basis for pastoral care and counselling. The article concludes with a critical reflection on pastoral care in a postmodern society. The method known as the hermeneutical model ("vertolkingsmodel") is evaluated in the light of pastoral care and counselling with women. Daniel J Louw's "Pastoraat asontmoeing: Ontwerp vir 'n basis teorie, antropologie, metode en terapie", is used as basis for this reflection.